RATA-RATA LAMA SEKOLAH (RLS) PADA PROVINSI SUMATRA TAHUN 2023 - Intan Amalia; Yulia Haerani, Zahra Aliipah, Sukmawaty Nurcahyani, Lydia Ismiati hakim, Riza Fahlapi (CV. ADIBA AISHA AMIRA, 2025)
This study aims to analyze the Average Years of Schooling (RLS) in six Sumatra Provinces in 2023, namely Aceh, North Sumatra, West Sumatra, Riau, Jambi, and South Sumatra. RLS data were collected and analyzed using descriptive statistical methods to provide a comprehensive picture of the condition of education in the region. The results of the analysis show that the average years of schooling of the population in these six provinces is 9.27 years, with a median of 9.145 years and a mode of 8.52 years. The standard deviation of 1.297 years indicates moderate variation in the data, while the skewness of 0.343 indicates a slightly right- skewed distribution of the data. The kurtosis of -0.165 indicates a distribution that is flatter than a normal distribution. These results provide important information for education planning and policy making in Sumatra. It is suggested that utilizing more sophisticated technology and statistical software can improve the accuracy and efficiency of data processing.